Oblikovanje sodobnega potrošnika - Godina-Golija, Maja (Etnolog. Nova vrsta (Ljubljana), 2008)
The provision of food is one of the basic activities of man. Even though modern food supply and production greatly differ from past forms and our food increasingly depends on bought and prepared food products, modern forms of food supply have not been researched yet from an ethnological viewpoint. The article deals with the principal characteristics of the food supply and production in Slovenia from the early 20th century to the present, the ways ofbuying and preparing food, food conservation and preparation of food stocks,and the share of expenditure on food in the family budget in the past and today.
Keywords: ethnology; etnologija; food; nutrition; prehrana; trade; trgovina; supply; preskrba; Slovenia; Slovenija; historical survey; zgodovinski pregledi